2021
DOI: 10.1002/cssc.202002873
|View full text |Cite
|
Sign up to set email alerts
|

Interface Engineering of Needle‐Like P‐Doped MoS2/CoP Arrays as Highly Active and Durable Bifunctional Electrocatalyst for Overall Water Splitting

Abstract: Developing a bifunctional water splitting catalyst with high efficiency and low cost are crucial in the electrolysis water industry. Here, we report a rational design and simple preparation method of MoS 2-based bifunctional electrocatalyst on carbon cloth (CC). The optimized P-doped MoS 2 @CoP/CC catalyst presents low overpotentials for the hydrogen (HER) and oxygen evolution reactions (OER) of 64 and 282 mV in alkaline solution as well as 72 mV HER overpotential in H 2 SO 4 at a current density of 10 mA cm À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(23 citation statements)
references
References 87 publications
0
23
0
Order By: Relevance
“…The binding energy at 399.58, 400.75, and 401.84 eV can be ascribed to pyridinic N, pyrrolic N, and graphitic N, respectively [51]. In Figure 3F, the C1s spectrum can be fitted into C═C (284.81 eV), CN (285.86 eV), and CO (288.4 eV) [52].…”
Section: Resultsmentioning
confidence: 99%
“…The binding energy at 399.58, 400.75, and 401.84 eV can be ascribed to pyridinic N, pyrrolic N, and graphitic N, respectively [51]. In Figure 3F, the C1s spectrum can be fitted into C═C (284.81 eV), CN (285.86 eV), and CO (288.4 eV) [52].…”
Section: Resultsmentioning
confidence: 99%
“…The above experimental results showed that the WO 3−x whiskers produced by the reaction of WC with CO 2 should play an important role. The in situ developed WC/WO 3−x heterostructure interface synergistically modulated the electronic structure and the charge transfer, favoring the acceleration of the HER electrochemical process and the maintenance of high stability [22,60,61]. The appropriate number and diameter of WO 3−x in WC/WO 3−x -900 lead to the best HER performance.…”
Section: Her Electrocatalytic Activitymentioning
confidence: 99%
“…Electrochemical impedance spectroscopic (EIS) results revealed that Ru/NC@WOC has relatively lower resistances than Ru/C and therefore a faster charge transfer. [34] We further show the Tafel plots of the kinetic current density (j k ) versus the overpotential (Figure 3b). The exchange-current density (j 0 ) was obtained from the micropolarization region (À 5 to 5 mV) by linear fitting through the Butler-Volmer equation.…”
Section: Electrochemical Activity Toward Alkaline Hormentioning
confidence: 99%
“…It is shown that the highly efficient HER kinetics on the Ru/ NC@WOC follows the Volmer-Heyrovsky mechanism associated with the electrochemical desorption of hydrogen, which is the rate-limiting step. [34] The solution resistance reflects the impedance between the working electrode and the reference electrode circuit, which is mainly affected by changes in the experimental setup (Figure S12), while the charge transfer resistance mainly explores the conductivity of the catalyst. As illustrated in Figure 6c, Ru/NC@WOC shows a much smaller semicircle than that of commercial Pt/C and the Ru/C benchmark in complex-plane plot, demonstrating Ru/NC@WOC has a smaller charge transfer resistance with higher conductivity during the HER catalysis.…”
Section: Electrochemical Activity Toward Alkaline Hermentioning
confidence: 99%